Needs Analysis For The Utilization of Artificial Intelligence In The Drafting of Regional Legal Products In Indonesia: A Case Study In The Provinces of West Java, Central Java, and East Java - Ende Hasbi Nassaruddin; Dian Rachmat Gumelar; Zaihan Harmaen Anggayudha; Jody Imam Rafsanjani; Wahyudi Wahyudi (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
In an increasingly advanced digital era, the use of Artificial Intelligence (AI) in the legislative process and the creation of legal products has become a significant innovation worth attention, especially for enhancing efficiency and accuracy. This study aims to analyze the use of AI from a siyasah dusturiyah perspective and analyze the need for AI utilization in the preparation of regional legal products in three main provinces of Indonesia: West Java, Central Java, and East Java. This research uses a qualitative method with a case study approach, involving secondary data analysis and interviews with policymakers and legal experts. The study findings indicate that the use of AI from a siyasah dusturiyah fiqh perspective can be understood as part of the development of contemporary ijtihad. In addition, the implementation of AI has great potential to reduce administrative burdens, accelerate the legislative process, and improve the quality of regulations. However, several challenges remain, such as the readiness of technological infrastructure, AI-related regulations, and resistance from several stakeholders. These findings provide recommendations for strategic steps that regional governments can take to optimize the use of AI in the preparation of legal products.